The Effect of Marketing Mix on Sales Volume at UD. Design Kencono - Marshyanda Putri Nurhidayah; Ety Dwi Susanti (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
Indonesia's economic growth is significantly influenced by small and medium industries (SMEs). In addition to creating jobs, SMEs encourage economic expansion in various regions, including rural areas. The purpose of this study was to analyze the influence of the marketing mix consisting of products, prices, locations, and promotions on sales volume in UD. Design Kencono Ponorogo. A type of associative research using a quantitative approach was used in this study. The population and sample are UD employees. Plan a Kencono of 50 people. The saturated sampling technique was used in this study because the population was less than 100. The type of data used is primary data, using data collection techniques through the distribution of questionnaires to UD employees. Design Kencono Ponorogo. Using multiple linear analysis techniques through SPSS version 26, to determine the influence of Marketing Mix indicators (Products, Prices, Locations, Promotions) on Sales Volume in UD. Design Kencono. The results of the F test study show that, where the Marketing Mix indicators in the form of Products (X1), Price (X2), Location (X3), and Promotion (X4) together have a significant effect on Sales Volume (Y). The results of the study in the T test, only Products (X1) and Price (X2) had a partial significant effect on Sales Volume (Y), while for Location (X3) and Promotion (X4) there was no partial significant effect on Sales Volume (Y). The results of the determination test showed that the Product, Price, Location, and Promotion variables had the ability of 50.9% to explain the Sales Volume variable, while other variables that were not included in this study accounted for the remaining 49.1%.